Comparing infrastructure of anganwadi centres under integrated child development services of urban and rural Bangalore: a cross sectional study - G., Abhijnana; Thangaraj, Selvi; T. S., Ranganath; ., Vishwanath (International Journal Of Community Medicine And Public Health, 2019)
Background: Anganwadi centres under integrated child development services is the largest Project in India to improve not only child health but reproductive, maternal and adolescent health. The aim of the present study is to compare the infrastructure of urban and rural anganwadi which is one of the basic need to provide quality services. Methods: A total of 30 anganwadi centres are involved in our study in which 20 are from rural and 10 are from urban field practice area of Department of Community Medicine, Bangalore Medical College and Research Institute, Bangalore. This study employed interview method with anganwadi worker’s and observation of anganwadi centre using pre-designed, semi structured questionnaire and checklist. Results: 85% of rural and 60% urban anganwadi centres have their own buildings to carry out the services. 20% of rural anganwadi centres lack fixed name boards compared to urban anganwadi centres. 55% of rural anganwadi centres and 90% of urban anganwadi centres lack separate storage for raw food materials. 15% of rural anganwadi centres lack functional toilet facility. 40% of rural anganwadi centres lack functional weighing machine. Conclusions: Anganwadi centres are remote contact point of health care system within the community. The infrastructure of anganwadi centre such as type of building, space for cooking and activities, availability of functional equipments ensure the quality service deliveries which in turn are enhanced by timely supervision from higher authorities.